Pembuatan Drying Conveyor dengan Pemanfaatan Panas Insinerator Untuk Pembangkit Listrik Tenaga Sampah (PLTsa) - Muhammad Faisal Novrio; Marno; Oleh (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The aim of this research is to develop an efficient drying conveyor that uses heat from the incinerator at the Waste-to-Energy Power Plant (PLTSa). The process involves decomposing waste in the incinerator, which generates heat to drive the drying conveyor. This conveyor speeds up the drying of the waste, reduces the water content and improves the waste-to-energy efficiency. This study also discusses the main components of the conveyor, factors affecting the design, the cost of manufacturing the conveyor, and provides a practical solution for developing waste management technology that is technically and economically better. The results showed that the designed drying conveyor has a total weight of 163,716 kg and a manufacturing cost of Rp. 7,627,800. The use of this drying conveyor has also been shown to increase the reliability of the system by reducing the frequency of maintenance and the risk of damage. From a cost perspective, this solution is more effective in the long run because it reduces operating costs and additional fuel consumption. In conclusion, the use of drying conveyors with incinerator heat recovery is an innovative step that supports the energy efficiency, sustainability and operational effectiveness of the PLTSa.